2006
DOI: 10.1111/j.1365-2893.2006.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography: a new surrogate marker of liver fibrosis influenced by major changes of transaminases

Abstract: Liver stiffness was measured by transient elastography (FibroScan) in 228 consecutive patients with chronic viral hepatitis, with (115) or without cirrhosis (113), to study its correlations with serum transaminases [alanine aminotransferase (ALT)], fibrosis stage and surrogate noninvasive markers of fibrosis (APRI, FORNS, FibroTest and hyaluronic acid). The dynamic profiles of serum transaminases and liver stiffness were compared by multiple testing in 31 patients during a 6-month follow-up. We identified 8.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
461
10
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 601 publications
(512 citation statements)
references
References 41 publications
38
461
10
3
Order By: Relevance
“…Indeed, as previously mentioned, the extent of necro-inflammatory activity has been shown to influence TE measurements in patients with viral hepatitis with a steady increase of liver stiffness values in parallel with the degree of histological activity [66,70,100]. Consistent with these results, the risk of overestimating liver stiffness values has been reported in case of ALT flares in patients with acute viral hepatitis or chronic hepatitis B [101][102][103], as well as in cases of extrahepatic cholestasis [104] or congestive heart failure [105].…”
Section: Limitationssupporting
confidence: 74%
“…Indeed, as previously mentioned, the extent of necro-inflammatory activity has been shown to influence TE measurements in patients with viral hepatitis with a steady increase of liver stiffness values in parallel with the degree of histological activity [66,70,100]. Consistent with these results, the risk of overestimating liver stiffness values has been reported in case of ALT flares in patients with acute viral hepatitis or chronic hepatitis B [101][102][103], as well as in cases of extrahepatic cholestasis [104] or congestive heart failure [105].…”
Section: Limitationssupporting
confidence: 74%
“…Some studies with transient elastography (19)(20)(21), SWE (21), and MR elastography (22,23) have concluded that the correlation between liver stiffness values and fibrosis stage is not affected by steatosis or necroinflammation. Other studies have suggested that inflammation, as suggested by elevated transaminase levels (24,25) or diagnosed at liver biopsy (26)(27)(28), affects transient elastography assessment of fibrosis. Similarly, steatosis has been reported to have no effect on acoustic radiation force imaging-based fibrosis assessment (29), whereas in several transient elastography studies, steatosis has been reported to have an effect on noninvasive fibrosis staging (28,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, severe inflammation and mechan-ical cholestasis can significantly increase hepatic stiffness, thus confounding the fibrosis readout. [104][105][106] Nonetheless, ultrasound elastography should prove useful for stratification of patients for inclusion into treatment studies.…”
Section: Noninvasive Means To Assess Liver Fibrosis and Fibrogenesismentioning
confidence: 99%